2021
DOI: 10.5271/sjweh.3972
|View full text |Cite
|
Sign up to set email alerts
|

Working life expectancies among individuals with type 1 and type 2 diabetes over a 30-year period

Abstract: Working life expectancies among individuals with type 1 and type 2 diabetes over a 30-year period by Nexø MA, Pedersen J, Cleal B, Andersen I, Bjørner JB This study predicts work life expectancies among individuals with type 1 and type 2 diabetes over 30 years. Work life losses for people with diabetes are substantial and characterized by social disparities. The results call for new strategies to prevent and manage individual and societal costs, particularly for individuals with less years of education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
3
10
1
Order By: Relevance
“…Previous studies have focused on WLE across educational or occupational groups (3,5,6,8,9,26,27), or on the influence of chronic diseases on WLE (2,(26)(27)(28). Their results are in line with the current study, showing the lowest WLE among persons with a low educational level and among workers with a chronic disease.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have focused on WLE across educational or occupational groups (3,5,6,8,9,26,27), or on the influence of chronic diseases on WLE (2,(26)(27)(28). Their results are in line with the current study, showing the lowest WLE among persons with a low educational level and among workers with a chronic disease.…”
Section: Discussionsupporting
confidence: 90%
“…It was suggested that diabetes could drastically affect working ability and work cessation 4 . A study that suggested significantly shorter working life expectancies and greater loss of working years in patients with diabetes 39 also supports our findings. Moreover, a reason why moderately long work is helpful in controlling diabetes is most likely due to the ability of the worker to maintain a routine.…”
Section: Discussionsupporting
confidence: 89%
“…The question of what impact living with diabetes has on work‐life has received a good deal of attention in recent years 1–7 . Focus on this question is timely, especially with respect to type 2 diabetes, where the global prevalence is on the rise and, in high‐income countries at least, aging population trends are pushing the mandatory age of retirement upwards.…”
Section: Introductionmentioning
confidence: 99%
“…
The question of what impact living with diabetes has on work-life has received a good deal of attention in recent years. [1][2][3][4][5][6][7] Focus on this question is timely, especially with respect to type 2 diabetes, where the global prevalence is on the rise and, in high-income countries at least, aging population trends are pushing the mandatory age of retirement upwards. Consequently, in the future, we can expect to see that more people with diabetes will be living with the condition while they ostensibly remain a part of the labour force.
…”
mentioning
confidence: 99%